2022
DOI: 10.3889/oamjms.2022.9042
|View full text |Cite
|
Sign up to set email alerts
|

Energy Intake and Food Restriction as Determinant Factors of Chronic Energy Deficiency among Pregnant Women in Rural Area of Sungai Sembilan, Riau, Indonesia

Abstract: BACKGROUND OF THE STUDY: Maternal malnutrition is a major public health problem in Indonesia which is shown by high prevalence of chronic energy deficiency (CED) among pregnant women. CED was expressed by the measurement of Mid Upper Arm Circumference (MUAC) showing value less than 23.5 cm. AIM OF THE STUDY: This study aimed to identify the factors associated with chronic energy deficiency among pregnant women in rural area, Riau Province. METHODOLOGY: A community- based cross sectional study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The inadequate energy intake might be caused by seasonal food availability, cultural prohibition, and lack of knowledge ( 79 81 ). Moreover, food restriction during pregnancy could cause mothers to have lower energy intake and lower consumption of diverse foods than the recommendation ( 82 ). A study by Ding et al found that energy and protein intakes among pregnant women decreased along with decreasing economic quintiles ( 83 ), which was also supported by a study done in Nepal ( 84 ) showing wealthier women were more likely to consume diverse diets than the poorer.…”
Section: Discussionmentioning
confidence: 99%
“…The inadequate energy intake might be caused by seasonal food availability, cultural prohibition, and lack of knowledge ( 79 81 ). Moreover, food restriction during pregnancy could cause mothers to have lower energy intake and lower consumption of diverse foods than the recommendation ( 82 ). A study by Ding et al found that energy and protein intakes among pregnant women decreased along with decreasing economic quintiles ( 83 ), which was also supported by a study done in Nepal ( 84 ) showing wealthier women were more likely to consume diverse diets than the poorer.…”
Section: Discussionmentioning
confidence: 99%